A multi-scale constitutive model for AlSi10Mg alloy fabricated via laser powder bed fusion - Lei, Mingqi (2025)
Additively Manufactured (AM) aluminum alloys find extensive applications in various fields due to their favorable properties. Numerical simulations play a crucial role in reducing experimental costs and enhancing reliability. Developing a reliable constitutive numerical model requires careful consideration of the hierarchical microstructure inherent in AM aluminum alloys. In response, a multiscale constitutive model has been formulated for the AlSi10Mg alloy, fabricated through laser powder bed fusion. This model incorporates crystal plasticity theory and micromechanics-based homogenization methods to establish representative volume elements at different length scales. These scales include the grain scale, polycrystalline scale, and macro scale, thus facilitating a seamless transition between them. The model is calibrated using macroscopic and average phase stress–strain relationships, demonstrating its capability to predict lattice strain in each phase. Additionally, this model incorporates a quantitative analysis of the effects of two-phase structure, melt pool structure, and porosity by adjusting microstructure parameters. The developed model is embedded into a user-defined material subroutine, providing an efficient approach to investigate microstructure-property relationships in AM alloys.